Development and Psychometric Evaluation of an A-Line Skirt Sewing Skills Assessment Instrument for Vocational Students - Zulfa Zulfa; Supriyadi Supriyadi; Adi Nur Cahyono (Journal of Research and Educational Research Evaluation, 2025)
The study aimed to examine the validity and reliability of an A-line skirt sewing skills assessment instrument for students. A Research and Development (R&D) method was employed to develop and evaluate the assessment instrument. The initial product was validated by four experts to obtain content validity, followed by instrument testing involving 25 tenth-grade fashion students at SMK Negeri 5 Kendal. Content validity was analyzed using Aiken’s V formula, while instrument reliability was examined through the Intraclass Correlation Coefficient (ICC) using SPSS version 27. The feasibility assessment demonstrated high validity across several aspects, including objectivity (0.85), systematic organization (0.91), construction (0.91), and language use (0.88). Item validity testing indicated satisfactory results. Of the 52 items tested, 8 items were identified as invalid, resulting in 44 valid and feasible items. The reliability coefficient reached 0.848, indicating adequate consistency and agreement among experts. The developed assessment instrument proved valid and reliable for measuring students’ A-line skirt sewing skills. The instrument contributes to vocational education assessment practices by providing a more objective, systematic, and standardized evaluation tool for sewing competency assessment.